Targeting STAT3 Abrogates Tim-3 Upregulation of Adaptive Resistance to PD-1 Blockade on Regulatory T Cells of Melanoma - Huang, Lili; Xu, Yu; Fang, Juemin; Liu, Weixing; Chen, Jianhua; Liu, Zhuqing; Xu, Qing (Frontiers in Immunology, 2021)
Background < 20% of melanoma patients respond to programmed cell death-1 (PD-1) blockade immunotherapies. Thus, it is crucial to understand the dynamic changes vibrant transformations in the tumor microenvironment (TME) after PD-1 blockade, for developing immunotherapy efficacy. Methods A genomic analysis was conducted by The Cancer Genome Atlas (TCGA) datasets and web platform TIMER2.0 datasets. Pathway enrichment analysis was performed using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. Peripheral blood mononuclear cells (PBMCs), regulatory T (Treg) cells and B16F10 melanoma mouse were used as models. The cellular and molecular characteristics and mechanisms of Treg cells in melanoma were assessed by performing gene expression studies, immunohistochemistry, RNA sequencing, and flow cytometry. Results Here, we evaluate the countenance of T cell immunoglobulin and mucin-domain containing-3 (Tim-3), various immunosuppressive factors within tumor infiltrated Treg cells after treated with anti-PD-1 or the indicator transduction and activator of transcription 3 (STAT3) inhibitors. Increased expression of Tim-3 is markedly observed within the tissues of the PD-1 blockade resistance of melanoma patients. Targeting STAT3 significantly boosts the response of resistant-PD-1 therapy within the melanoma mouse model. Mechanistically, the manifestation of STAT3 decreases the expression of Tim-3 and various cytokines in the purified Treg cells from individual PBMCs and murine melanoma model, limiting the immunosuppression of Treg cells. Conclusions Our findings indicate that Tim-3 expression on Treg cells within the TME is STAT3-dependent, providing support to STAT3 as a target and enhancing the immunotherapy for patients suffering from melanoma.